Migration Policy in Albania: Institutional Aspects - Stanislav A. Gorokhov; Ruslan V. Dmitriev (Современная Европа)
After the fall of the communist regime Albania turned from a closed country into a country of net emigration. The article examines the evolution of Albanian migration policy from 1990 to 2022. The purpose of the study is to identify the approaches to the regulation of international migration in the context of the integration of Albania into the EU. The research is based on the state and supranational sources in the field of migration: legislative and regulatory acts, strategies, action plans, international agreements. The period under consideration is divided into two almost equal parts in relation to the level of participation of Albania in the regulation of migration. The first period (until the mid-2000s) is characterized by a relatively passive stance, relying primarily on external forces which regulate migration from Albania, such as other countries of the region and the EU. With the adoption of the Strategy for Migration Management in 2005 Albania took a more active stance, focused, on the one hand, on comprehensive and multidirectional interaction with the Albanian diaspora and, on the other, on reducing emigration by creating new jobs. It is revealed that the measures taken to return the representatives of the diaspora to the country and reduce the emigration activity of the current inhabitants of Albania are not enough. The diaspora plays a significant role in the economy of Albania, however, it does not seek re-emigration. The effect of job creation was largely offset by the European migrant crisis.